Fabrication of Ultrathin Large-area Dielectric Membrane Stacks for use as Interference Filters. (2016) - Ghaderi, M.; de Graaf, G.; Wolffenbuttel, R.F.
Abstract: The design and CMOS-compatible fabrication of stacked dielectric membranes are presented. The structures are intended for use as airgap-based interference filters operating in the UV-visible spectrum. In optical filters, maximizing the fill-factor, i.e. the ratio of the active area to the total area of the filter, is essential, which calls for minimum dimensions of the anchoring pillars and the openings that are required for the fabrication of the structures. This requirement necessitates the fabrication of large area free- standing membranes. Maintaining flatness over such a large area (> 1000μ m 2 ) membrane, as required by the optical application (deformation< λ/10), is challenging. While the thickness of the free-standing membrane is defined by the optical specification, the residual stress is the main force acting on the structure. Although an overall tensile residual stress can effectively stretch the membrane, the presence of a residual stress gradient causes the membrane to deform. Furthermore, a high residual stress results in the rupture of the membrane. These challenges in the fabrication of airgap-dielectric Bragg gratings are discussed. Higher-order optical designs were investigated to simultaneously satisfy both the mechanical and optical requirements. Bragg reflectors with one and two periods have been fabricated and characterized. The preliminary results are presented.